Sub-Millimetre Positron-Emission Particle Tracking Using a CdZnTe Semiconductor Array - Hyslop, Nicholas (Department of Physics, 2022)
The Positron Emission Particle Tracking (PEPT) technique has been in development in Cape Town since 2009, and typically allows the tracking of a 1 mm diameter positron-emitting source travelling at 1 m/s with precision around 1 mm at kHz rates. Conventionally, PEPT utilises large, high efficiency scintillator detectors and relies on high data-rates obtained from high activity tracer particles to achieve the quoted performance. However, as we look to apply the technique to more challenging liquid and mixed phase systems, smaller tracer particles are required (of the order 10 µm) which are necessarily limited in attainable activity and therefore applicability in current systems. This dissertation investigated the use of pixelated room-temperature semiconductor CdZnTe detectors with high pixel resolution to implement PEPT. Using a PolarisJ CZT detector module array built by H3D Inc. (Ann Arbor, MI, USA) with a field-of-view of 40 × 60 × 20 mm3 , a positron-emitting 22Na source (1 mm diameter) with an activity of 20 kBq was located in three-dimensional space with a radial location uncertainty of < 600 µm (68% coverage) and location rate of ≈ 0.3 Hz. A 68Ga source (160 µm diameter) with an activity of 1 MBq was located with a radial position uncertainty of < 800 µm (68% coverage) and location rate of ≈ 10 Hz. A 37 kBq 22Na tracer was tracked with sub-millimetre precision undergoing circular motion at radii between 0.5 - 20 mm and speeds between 0.25 and 15 mm/s. We have showed sub-millimetre tracking of tracer particles with tracer activities orders of magnitude lower than currently possible using conventional PEPT systems. A potential application of this work is in providing on-line beam diagnostics in proton radiotherapy. The PEPT technique was therefore applied to Geant4 simulation data of a 55 MeV and 200 MeV proton beam passing through an organic target to locate the beam-line with uncertainties within the incoming beam width. Such proton beams produce positron emitters at activities too low to measure with conventional scintillators. With the current CZT arrays already in use for dose verification imaging, incorporating such beam-tracking to improve image quality can be easily implemented in future.